"Sicut lilium inter spinas". Floral Metaphors in Late Medieval Marian Iconography from Patristic and Theological Sources - Salvador González, José María (Eikón / Imago, 2014)
This paper proposes an interpretation of the flowers and other plant motifs present in some late medieval images of four Marian themes: the Virgin Enthroned with Child, the Virgin of Humility, the Sacra Conversazione and the Coronation of the Virgin. By supplementing certain unjustified conventions that, without any argument, see these flowers as natural symbols of Mary’s love or virginity, our iconographic proposal is based on multiple evidence by prestigious Church Fathers and medieval theologians. By commenting some significant passages of the Old Testament, all of them praise the Mother of the Savior in terms of flowers and plants as metaphors for her holiness and virtue. Thus, on the basis of a solid patristic and theological tradition, this paper attempts to interpret these botanic elements as symbolic figures of purity, humility, charity, sublimity of virtue and absolute holiness of Mary and, as the essential core, her perpetual virginity and virginal divine motherhood.